2002
DOI: 10.4315/0362-028x-65.7.1110
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Campylobacter jejuni in Biofilms Isolated from Chicken Houses

Abstract: Campylobacter jejuni is a thermophilic and microaerophilic enteric pathogen associated with poultry. Biofilms may be a source of C. jejuni in poultry house water systems since they can protect constituent microorganisms from environmental stress. In this study, the viability of C. jejuni in biofilms of gram-positive chicken house isolates (P1, Y1, and W1) and a Pseudomonas sp. was determined using a cultural method (modified brucella agar) and direct viable count (DVC). Two-day biofilms grown on polyvinyl chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 36 publications
2
65
1
Order By: Relevance
“…Experimental evidences suggest that under certain conditions C. jejuni generates viable but non-culturable forms, especially in Biofilms derived from aviaries (15). Hiett et al (7) also demonstrated 70% Campylobacter sp in eggs by direct Polymerase Chain Reaction (PCR), but these eggs were 100% negative with the traditional culture methods, suggesting that Campylobacter could be present in eggs, however, without it being possible to isolate it.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidences suggest that under certain conditions C. jejuni generates viable but non-culturable forms, especially in Biofilms derived from aviaries (15). Hiett et al (7) also demonstrated 70% Campylobacter sp in eggs by direct Polymerase Chain Reaction (PCR), but these eggs were 100% negative with the traditional culture methods, suggesting that Campylobacter could be present in eggs, however, without it being possible to isolate it.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that under such conditions C. jejuni generates forms that are viable but nonculturable, especially in the presence of biofilms derived from poultry houses (101). The survival of such forms for periods of up to 4 months has been recorded (79), but survival times appear to vary with water temperature, strain, the aquatic system used, and previous growth conditions (11,98,99).…”
Section: Sources Of Poultry Colonizationmentioning
confidence: 99%
“…Thus, they are widely disseminated in the farm environment, and they can be concentrated in raw poultry meat. Because of its susceptibility to multiple environmental stresses (e.g., temperature, relative humidity, and air composition), it is known that Campylobacter does not grow outside its host, but is able to survive in litter [17], in sewage [1], in biofilms formed in the water distribution systems of poultry houses [12], and for more than two weeks in feces [32]. The reduction of Campylobacter contamination at different levels of the poultry production chain, especially at the primary production level, should decrease the risk of human infection.…”
mentioning
confidence: 99%